Tooth-bleaching procedures and their controversial effects: A literature review - Mohammed Q. Alqahtani (Elsevier, 2014)
Aim: This review article will help clinicians improve their understanding of the history of bleaching procedures, bleaching types, components, mechanisms, and their effects on soft tissue, tooth structures, resin composite, and bonding. Methods: The controversial issues about bleaching procedures and their effects are reviewed. Additionally, the consequences of pre- and post-bleaching on the bonding potential of composite resin restorations to tooth structure are discussed. Conclusion: The overall goal of the paper is to help reduce risks for patients. Keywords: Bleaching, Pre-bleaching, Post-bleaching, Bonding